(untitled) (Studia Prawnicze / The Legal Studies, 2002)
Omawiany w artykule Protokół dotyczący udziału dzieci w konfliktach zbrojnych oraz Protokół dodatkowy dotyczący handlu dziećmi, prostytucji dzieci oraz pornografii dziecięcej nie są wole od wad. Zawarta w nich możliwość składania zastrzeżeń może jeszcze bardziej osłabić ich działanie. Niewielką pociechą jest przyznanie Komitetowi Praw Dziecka możliwości kontroli stosowania protokołów. Komitet już dziś ma duże zaległości w rozpatrywaniu raportów i nie dziwi fakt, iż dąży on do poszerzenia swego składu. Dobrze więc, że taką kontrolę ustanowiono, od razu nasuwa się jednak pytanie o jej skuteczność. Pomimo tych mankamentów przyjęte protokoły stanowią niewątpliwie krok w kierunku umocnienia i rozszerzenia ochrony praw dziecka. The Protocol on the Involvement of Children in Armed Conflict, which is discussed in the article, and the Additional Protocol on the Trafficking of Children, Child Prostitution and Child Pornography are not without their flaws. The opportunity to make objections contained in them may further weaken their effect. It is of little consolation that the Committee on the Rights of the Child is given the opportunity to review the application of the protocols. The Committee already has a large backlog of reports and it is not surprising that it is seeking to expand its membership. It is therefore good that such inspection has been established, however, the question immediately arises as to its effectiveness. Despite these shortcomings, the adopted protocols undoubtedly represent a step towards strengthening and extending the protection of children’s rights.